High-Resolution Drought Detection Across Contrasting Climate Zones in China - Ji Li; Guoyong Leng; Karim Pyarali; Jian Peng (Remote Sensing)
Droughts have been exacerbated by climate change, posing significant risks to ecosystems, hydrology, agriculture, and human society. In this paper, we present the development and evaluation of a high-resolution 1 km SPEI (Standardized Precipitation-Evapotranspiration Index) dataset to enhance drought monitoring at finer spatial scales. The high-resolution SPEI datasets, derived using high-resolution TPDC precipitation and satellite-based MODIS potential evapotranspiration data, were compared with a coarse-resolution 50 km SPEI dataset derived from CRU measurements, as well as vegetation health indices (VHIs) and root zone soil moisture (SM), over two climatically contrasting regions in China: Northeast China (NEC) and Southwest China (SWC). The evaluation highlights the MODIS-based high-resolution SPEI’s ability to capture regional drought dynamics and improved correlation with vegetation and soil moisture dynamics. NEC, with its relatively flat topography and recent experience of significant droughts, and SWC, characterized by complex terrain and high precipitation variability, provided ideal testbeds for examining the performance of the 1 km SPEI. The results demonstrate that the high-resolution dataset offered superior spatial detail in detecting drought conditions, making it valuable for agricultural planning and water resource management in diverse climates.